Case Report: The Medical and Surgical Management of an Infant With Extreme Prematurity and Fetus-In-Fetu - Sun, Raphael C.; Cheng, Lily S.; Shah, Rita H.; Lohmann, Pablo; Cortes-Santiago, Nahir; Ketwaroo, Pamela D.; Keswani, Sundeep G.; King, Alice; Lee, Timothy C. (Frontiers in Surgery, 2022)
Fetus-in-fetu (FIF) is a rare congenital anomaly where a parasitic twin is within the body of a host twin. FIF is reported to occur in 1:500,000 live births. Herein, we report the first case of the medical and surgical treatment of a FIF patient who was born with extreme prematurity at 25-weeks gestation. With the multi-disciplinary coordination of neonatology, surgery, and interventional radiology, the patient was able to achieve a window of medical stability 4 weeks after birth. A decision was made at that time to proceed with an intra-abdominal and perineal resection of the FIF. The FIF was successfully resected and the patient was able to recover from the operation, with eventual discharge from the NICU. In conclusion, extreme prematurity and FIF may be amenable to surgical resection and a multi-disciplinary approach is crucial to achieve the desired outcome.